Unique marine PermianTriassic boundary section from Western Australia - Thomas, B. M.; Willink, R. J.; Grice, Kliti; Twitchett, R. J.; Purcell, R. R.; Archbold, N. W.; George, A. D.; Tye, S.; Alexander, Robert; Foster, C. B.; Barber, Cindy (Blackwell Publishing Asia, 2004)
A unique marine Permian-Triassic boundary section containing rich oil source rocks has been continuously cored in a petroleum borehole from the Perth Basin of Western Australia. Such sequences, which provide a biostratigraphic and environmental record at the time of the largest extinction event of the past 500 million years, are globally rare, and this is the first to be documentedin Australia. Throughout geological history there have been periods of global marine anoxia that commonly resulted in the widespread deposition of petroleum source rocks, most notably in the mid-Cretaceous and Late Jurassic. An apparent paradox is that, previously, source rocks have not been recognised in association with the Permian-Triassic boundary, despite widespread marine anoxia at this time. The Perth Basin source rocks contain abundant and unusual biomarkers, apparently related to the highly specialised and limited biota that flourished in the aftermath of the end-Permian extinction event. Local conditions may have favoured source-rock development, either due to higher productivity resulting from coastal upwelling or through enhanced preservation under strongly anoxicconditions.